2015
DOI: 10.1103/physreve.91.022124
|View full text |Cite
|
Sign up to set email alerts
|

Translational diffusion of water inside hydrophobic carbon micropores studied by neutron spectroscopy and molecular dynamics simulation

Abstract: When water molecules are confined to nanoscale spacings, such as in the nanometer size pores of activated carbon fiber (ACF), their freezing point gets suppressed down to very low temperatures (∼ 150 K), leading to a metastable liquid state with remarkable physical properties. We have investigated the ambient pressure diffusive dynamics of water in microporous Kynol TM ACF-10 (average pore size ∼11.6Å, with primarily slit-like pores) from temperature T = 280 K in its stable liquid state down to T = 230 K into … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…They observed that the self-diffusion coefficient increases with the temperature and is higher for lower adsorption loadings. Diallo et al [212] also simulated water confined by activated carbon fibers. They evaluated the diffusion coefficient of supercooled water (220 ≤ T ≤ 280 K) and compared the results with experimental data from quasi-elastic neutron scattering.…”
Section: Carbon Compoundsmentioning
confidence: 99%
“…They observed that the self-diffusion coefficient increases with the temperature and is higher for lower adsorption loadings. Diallo et al [212] also simulated water confined by activated carbon fibers. They evaluated the diffusion coefficient of supercooled water (220 ≤ T ≤ 280 K) and compared the results with experimental data from quasi-elastic neutron scattering.…”
Section: Carbon Compoundsmentioning
confidence: 99%
“…The interaction of a fluid with either a 2D or 3D substrate gives rise to interesting properties at the interface which are absent in the bulk phase [36]. Pore size, shape, connectivity and surface roughness (fractality) may produce somewhat different results compared to a simple 2D surface as pore dimensionality is reduced to the point where the sorption layers start to overlap [37][38][39].…”
Section: Introductionmentioning
confidence: 98%
“…Experiments in slit pores show that water forms layers parallel to the walls [72]. Computer simulations of water between two nanoscopic hydrophobic plates reveal that these layers correspond to local minima in the free-energy profile as a function of the plate-plate separation w [73] and that the water mobility in a hydrophobic slit pore monotonically increases as w becomes larger [74,75,76,77,78,79,80,81,82,83]. Similar results hold for water confined in graphite [84] and quartz [45,46,76], with freezing of the dynamics at sub-nm confinement.…”
Section: Introductionmentioning
confidence: 99%